(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2023)
Background & purpose: Work -related musculoskeletal disorders have been known to affect workers in a wide variety of occupations and are major causes of lost time from work, worker’s disability, increase in compensation claims and health care costs. The pattern of work-related musculoskeletal disorders has been reported to vary among different occupational groups. Tailoring involves monotonous, highly repetitive tasks like cutting, assemble, pressing and finishing performed in sitting working posture with upper back curved and head bent over the sewing machine. The aim of this study is to assess the prevalence of musculoskeletal disorders and risk of low back pain among self-employed female tailors. Methods: A cross sectional study was conducted at selected places of Bengaluru. 70 subjects were selected based on the inclusion and exclusion criteria and were screened for work-related musculoskeletal disorder using Nordic Musculoskeletal Disorder Questionnaire and low back pain using Modified Oswestery lower back disability index. Results: The results were statistically analyzed. The study found high rate of musculoskeletal disorders among self-employed female tailors. More than 79.2% of tailors suffered from musculoskeletal pain and lower back were the most prevalent site. Conclusion: The study found high rate of musculoskeletal disorders among self-employed female tailors. More than 79.2% of tailors suffered from musculoskeletal pain and lower back were the most prevalent site. Frequent breaks during work period and back support would reduce the musculoskeletal stress on lumbar region. Based on the observations made, the study concluded that there is ample scope for ergonomic improvement keeping in view the need for maximum comfort to the tailors to promote their health and well-being and enhance their productivity and quality of work.